Implementasi Pendidikan Berbasis Multikultural: Membentuk Karakter Siswa Menuju Indonesia Emas 2045 - Umiati*, Umiati; Sufi, Ivan Septian (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2024)
Cultural and religious diversity in Indonesia, believed or not, will be able to cause problems that are now facing this nation. Corruption, Collusion, Nepotism, thuggery, political strife and the most prevalent at this time is bullying in schools and outside schools. The implementation of Multicultural-Based Education offers an alternative through the application of the concept of education to the use of diversity in society, especially in students. This education is also important to be applied to children from an early age to grow into a generation tolerant of diversity. This type of education can be given directly by the school, through teachers and applied by parents at home. The novelty in this article is to find a new path in the Implementation of Multicultural-Based Education to shape the character of students towards a Golden Indonesia 2045. The purpose of this study is to describe the results of research related to multicultural education and student character building in education in Indonesia. The findings in the articles can make the basis for formulating new paths or providing recommendations in the implementation of multicultural-based education to shape student character towards Golden Indonesia 2045. The method used in this study is a literature review of Indonesian and English articles in 2018-2022 sourced from google scholar search sites, National Journal (Garuda) and Journal of Education Management with the keywords "Multicultural Education", "Education Implementation" and "Student Character". The data analysis procedure was carried out based on a qualitative approach, research findings showed that the implementation of Multicultural Education had an important positive influence on student character. Students will experience increased understanding and appreciation of differences, both in terms of culture, religion, and social values. Multicultural education must be taught from an early age by teachers through integrating into subjects, using various strategies and variations inside and outside the classroom and creating a culture of equal treatment without differentiating in the school environment.